Daily Glucocorticoid Replacement Dose in Adrenal Insufficiency, a Mini Review - Caetano, Celina M.; Malchoff, Carl D. (Frontiers in Endocrinology, 2022)
The Endocrine Society Guidelines and recent reviews of adrenal insufficiency (AI) recommend a daily glucocorticoid replacement dose of 15 to 25 mg with a midpoint of 20 mg of hydrocortisone (HC) (alternatively 3 to 5 mg prednisolone) in divided doses in otherwise healthy individuals with AI. In contrast, a daily glucocorticoid replacement dose of 4.3 to 26 mg/d HC with a midpoint of 15 mg/d is predicted from current measurements of daily cortisol production rates and oral HC bioavailability. The higher HC doses recommended in the current guidelines may result in glucocorticoid overtreatment of some AI patients and associated long-term adverse outcomes. A titration method for determination of the individual patient’s daily glucocorticoid replacement dose and the impact of lower doses are reviewed. Future related research questions are identified.